Effects of different concentrations of municipal wastewater on seed germination and seedling performance of three rice (Oryza sativa L.) varieties - Gassama, Umaru Mohamed (2015)
Agriculture is the largest user of fresh water for irrigation. As the demand of fresh water is increasing, there is a need to recycle municipal wastewater for agricultural activities. The objective of the study was to determine the effect of different concentrations (0, 2.5, 5, 10, 25, 50, and 100%) of untreated and treated municipal wastewater on seed germination and seedling performance of fresh and aged rice seeds, seedling nutrient uptake and seedling chlorophyll content. Laboratory experiments were conducted using three Malaysian rice varieties, MR219, MR220 and MR253. This study revealed varying responses of rice for germination percentage, germination rate index, seedling length, seedling fresh weight, seedling dry weight, root volume, root surface area, seedling vigour index, root:shoot ratio and percentage phytotoxicity when the seeds were irrigated with different concentrations of municipal wastewaters. The seeds imbibed in untreated wastewater gave higher values of seed germination and seedling growth and development than treated wastewater. Lower municipal wastewater concentrations (2.5-25%) showed promoting effect on rice seed germination while higher wastewater concentrations (50-100%) retarded seed germination and crop growth and development. Significant difference (p<0.05) was observed between untreated and treated wastewaters for germination rate index, seedling length, seedling fresh weight, root volume and root surface area. All the varieties tested showed varying responses to germination percentage, seedling length, seedling fresh weight, seedling dry weight, root volume and root surface area when imbibed with municipal wastewater for aged and fresh rice seeds. However, no significant difference was observed among the three rice varieties for germination rate index and seedling length for aged seed. Municipal wastewater contains essential nutrients for plant growth and development. Nitrogen, phosphorous, potassium, calcium, magnesium, zinc, iron, copper and manganese were high in the untreated municipal wastewater compared to treated municipal wastewater. Rice seed imbibed with untreated municipal wastewater had more nutrients uptake than treated municipal wastewater as detected in the seedlings in this study. Furthermore, higher concentration of municipal wastewater >50% inhibit nutrients uptake while lower concentration of municipal wastewater <25% stimulate nutrients uptake. The study shows that P, K, Mg, Mn and Zn were sufficient for the rice seedling while N and Ca were far from optimum level for rice but Cu and Fe were excess and toxic to the rice seedlings. The municipal wastewaters showed inhibitory effect on chlorophyll content. The inhibition effect was observed at >50% concentration of both untreated and treated municipal wastewater while promoting effects were observed at lower <25% concentration. Positive and significant correlation was indicated between parameters of rice seed germination; seedlings performance and chlorophyll content while all the nutrients elements were negatively and highly correlated with quantity of municipal wastewater. Therefore, municipal wastewater can be used to raise quality seedlings without affecting seedling growth. The results indicated that untreated wastewater is better for rice seed germination and seedling performance than treated wastewater. This can be due to the high amount of nutrient in the untreated municipal wastewater which triggers the physiological process of the seeds that leads to increase in seedling growth and development. This study indicates that municipal wastewater of < 25% concentration is safe enough to be used in irrigation for rice production.